2021
DOI: 10.1017/s1041610221000168
|View full text |Cite
|
Sign up to set email alerts
|

Excessive sleep increased the risk of incidence of cognitive impairment among older Chinese adults: a cohort study based on the Chinese Longitudinal Healthy Longevity Survey (CLHLS)

Abstract: Study objectives: Based on a cohort from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), we aimed to evaluate the relationship between sleep duration and the incidence of cognitive impairment among older Chinese adults. Methods: We conducted a prospective analysis based on 3692 participants from the CLHLS at baseline (in 2011), and as a 3-year follow-up (till 2014), 531 participants (14.4%) had cognitive impairment, which was defined as a Mini-Mental State Examination score &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
0
16
2
Order By: Relevance
“…The current study noted that among individuals with primary and above education, excessive sleep duration was linked to cognitive impairment (Zhang et al, 2021). Education may contribute to 'cognitive reserve' or the capacity of the brain to buffer against age-related decline and pathologic damagethus delaying the onset of noticeable clinical symptoms (Stern, 2012).…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…The current study noted that among individuals with primary and above education, excessive sleep duration was linked to cognitive impairment (Zhang et al, 2021). Education may contribute to 'cognitive reserve' or the capacity of the brain to buffer against age-related decline and pathologic damagethus delaying the onset of noticeable clinical symptoms (Stern, 2012).…”
mentioning
confidence: 70%
“…In conclusion, the Zhang et al (2021) study and the diverse cohort of older Chinese study participants provide an important contribution to the growing knowledge regarding sleep duration and cognitive impairment. However, further exploration of education, language, and lifespan changes are warranted to establish these causal factors and identify which individuals would be most likely to benefit from potential preventative sleep-related interventions or use of sleep as an early risk factor for future cognitive impairment.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However, as we mentioned above, the public education has shift to dementia prevention and early detection, newly identified risk factors should be taken into consideration. For example, Zhang et al found that excessive sleep ( ≥ 10 hours/day) may increase the risk of cognitive impairment in older individuals (OR = 1.309, 95% CI: 1.019-1.683) (Zhang et al, 2022). To overcome the shortcoming of the structure questionnaire, the qualitative design might be considered in future studies, which could provide a more detailed description of participants' perceptions, thoughts, and understandings of dementia.…”
mentioning
confidence: 99%